Patient-reported outcome measures in subarachnoid hemorrhage: A systematic review. (4th June 2019) - Nobels-Janssen, Edith; van der Wees, Philip J.; Verhagen, Wim I.M.; Westert, Gert P.; Bartels, Ronald H.M.A.; Boogaarts, Jeroen D.
Abstract : Objective: Patient-reported outcomes (PROs) are aspects of a patient's health status and are considered important for stimulating patient-centered care. Current outcome measures in clinical care for patients with aneurysmal subarachnoid hemorrhage (aSAH) are insufficient to capture PROs. In this systematic review, we aimed to summarize the evidence regarding the quality of patient-reported outcome measures (PROMs) in aSAH patients. Methods: We performed a systematic review of the literature published from inception until October 29, 2018, in PubMed, the Cochrane Central Register of Controlled Trials, and EMBASE. Eligible studies had to evaluate measurement properties and capture PROs in aSAH patients. The quality of the studies and measurement properties were assessed using the consensus-based standards for the selection of health status measurement instruments (COSMIN) checklist. The review protocol was registered with PROSPERO (CRD42018058566). Results: We identified 9 articles that reported the assessment of 7 different disease-specific and generic PROMs used for aSAH patients, including 5 that focused on the Stroke-Specific Quality of Life Scale (SS-QoL). The methodologic quality of the validation processes used was generally doubtful. None of the PROMs complied with current standards for content validity. Conclusions: Due to the low quality of evidence for the measurement properties, the evidence base for selecting a suitable PROM for use with aSAH patients is insufficient. Given the specific long-term consequences of aSAH, we consider a disease-specific PROM the most appropriate, with SS-QoL the most suitable PROM currently available.